Oral feedback in face-to-face conferencing on EFL postgraduate students' thesis drafts - Abdulkhaleq, Mohammed M. Ali; Tan, Bee Hoon; Abdullah, Faiz Sathivellu (Malaysian English Language Teaching Association, 2013)
Oral feedback (OFB) in face-to-face conferencing plays a crucial role in the supervision process as it helps in scaffolding EFL postgraduate students‟ thesis work, and in the related academic socialization.Yet, the importance of OFB at the postgraduate level has not been specifically addressed or considered adequately. In view of this gap in the literature, this paper reports a study related to the problems EFL supervisees encounter in OFB face-to-face conferencing.Participants were international students from Yemen studying at a Malaysian public university and specializing in English language studies. This paper discusses the major findings obtained from an analysis of OFB face-to-face conferencing between supervisors and supervisees. The results showed that in theOFB conferencing, supervisors tended to dominate the conversations with their students. Students‟ lack of fluency in the English language that might be due to a heightened anxiety level in the face-to-face conferencing was a major reason behind passing their turns in the conversations to their supervisors. Another major finding of the study was the lack of rapport between the supervisors and supervisees during the OFB conferencing .The study indicated that OFB face-to-face conferencing was of limited use to postgraduate EFL students in helping them revise their thesis drafts.